High resolution mass approach to characterize refrigerated black truffles stored under different storage atmospheres. (December 2017) - Longo, Edoardo; Morozova, Ksenia; Loizzo, Monica R.; Tundis, Rosa; Savini, Sara; Foligni, Roberta; Mozzon, Massimo; Martin-Vertedor, Daniel; Scampicchio, Matteo; Boselli, Emanuele
Abstract: Freshly harvested Tuber melanosporum samples were packed and stored at 4 °C under reduced atmospheric pressure or modified atmosphere for four weeks. Multivariate analysis was employed to correlate the antioxidant power of the ethanolic extracts of the samples with the chemical composition determined by high resolution mass spectrometry. High performance liquid chromatography coupled with a coularray detector was applied to select the chemical species associated with the antioxidant power. Four classes of chemical compounds were investigated in more detail by a targeted approach: derivatives of glutathione, adenine (such as S- adenosyl-homocysteine), oxidized linoleic acid and ergosterol. Adducts containing glutathione and adenine with oxidized linoleic acid were observed in TM for the first time and can be considered markers of freshness of the product. S- adenosyl-homocysteine, the acetyl-carnitine adduct with cysteinyl-glycine and several oxidized linoleic acid derivatives were among the markers of degradation. Graphical abstract: Highlights: Untargeted HRMS described the quality of refrigerated black truffles over storage. Targeted HRMS focused on compounds related to the antioxidant activity. Adducts of glutathione, adenine and oxidized linoleate are markers of degradation.